Development and Psychometric Evaluation of an Instrument to Assess Physical Activity Participation Behavior Among Chinese Patients with Chronic Obstructive Pulmonary Disease - Liao Y; Wang H; Zhan Y; Liu Y; Wang W; Ke H; Lan F; Zhi Q; Li W; Yu J (International Journal of COPD)
Yuanyu Liao,1,2,* Huan Wang,3,* Yuxin Zhan,3 Yunfang Liu,4 Weiwei Wang,5 Hui Ke,6 Fenfen Lan,2 Qiongge Zhi,2 Wang Li,2 Jiaohua Yu1 1Department of Nursing, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei, People’s Republic of China; 2School of Nursing, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei, People’s Republic of China; 3Department of Neurosurgery, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei, People’s Republic of China; 4Department of Thoracic Surgery, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei, People’s Republic of China; 5Department of Gastrointestinal Surgery, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei, People’s Republic of China; 6Department of Wound Care Center, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jiaohua Yu, Department of Nursing, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, 1277 Jiefang Avenue, Wuhan, Hubei, 430022, People’s Republic of China, Email yujiaohua2008@126.comPurpose: This study aimed to develop and evaluate a psychometrically reliable tool specifically designed to assess physical activity participation behavior in COPD patients in China.Patients and Methods: Using the Motivation-Opportunity-Ability (MOA) model as a framework, a scale was developed and evaluated through literature and guideline reviews, qualitative research, interdisciplinary expert consultations (n=21), and a pilot trial (n=50). A sample of COPD patients diagnosed over a year was randomly divided into two groups for exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) to test the factor structure. The scale’s content validity, internal consistency and test-retest reliability were further assessed.Results: 433 COPD patients from four hospitals in a city in China participated in this study. The final scale included 32 items and demonstrated good internal consistency, with a Cronbach’s α of 0.956 and a test-retest reliability of 0.777. The EFA identified four dimensions, with factor loadings ranging from 0.530 to 0.799, explaining 60.338% of the total variance: Motivation (5 items), Opportunity (12 items), Ability (9 items), and Behavior (6 items). The CFA confirmed that the four-dimensional model fit the data well: χ²/df = 1.891, standardized root mean residual (SRMR) = 0.0497, root mean square error of approximation (RMSEA) = 0.064, comparative fit index (CFI) = 0.927, Tucker-Lewis index (TLI) = 0.921.Conclusion: The Physical Activity Participation Behavior Scale for COPD patients demonstrated good reliability and validity and can be used to assess physical activity participation in individuals with COPD.Keywords: COPD, instrument, reliability, validity